Low density lipoprotein receptor-dependent prostaglandin synthesis in Swiss 3T3 cells stimulated by platelet-derived growth factor. - Habenicht, A J (1986)
We studied the effects of human plasma lipoproteins on the synthesis of prostaglandin (PG) E2 in Swiss 3T3 mouse fibroblasts. Quiescent cells, maintained in medium deficient in both platelet-derived growth factor (PDGF) and lipoproteins, synthesized less than 8 ng of PGE2 per 10(6) cells per 22 hr, and this rate did not change in response to the addition of lipoproteins. In contrast, PDGF-stimulated cells, incubated in medium deficient in lipoproteins, synthesized 45-110 ng of PGE2 per 10(6) cells during the same period of time, and this rate increased 2- to 5-fold in the presence of added low density lipoproteins (LDL). This stimulatory effect of LDL seemed to depend on LDL receptor-mediated binding, uptake, and degradation of the lipoproteins because: both LDL and very low density lipoproteins were active, whereas high density lipoproteins were not; low concentrations of LDL were effective; the effect of native LDL was blocked by acetylation of the LDL; PDGF increased both the expression of LDL receptors and the cellular uptake of LDL; chloroquine blocked the effect of LDL but not that of exogenous arachidonic acid. These results provide evidence that the LDL pathway is critically linked to PG synthesis in PDGF-stimulated cells.